2011
DOI: 10.1097/sap.0b013e3181d50dda
|View full text |Cite
|
Sign up to set email alerts
|

Staged Cleft Sternum Repair Using Dermal Allograft and Synthetic Mesh

Abstract: Cleft sternum is a rare congenital chest deformity that develops during the first trimester. Failure of the process of midline mesenchymal strip fusion leads to absence of the sternum, resulting in cleft formation. Multiple surgical approaches have been described in the closure of sternal clefts. An optimal surgical approach is still debatable. We describe 2 cases of complete sternal clefting treated with staging of the repair. Dermal allograft and synthetic mesh along with myofasciocutaneous flaps are used a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Multiple approaches to sternal cleft repair have been described, most of which used a single-stage technique, and some included the use of different types of mesh [13,14]. One recent case series reported staged sternal cleft closure in 2 infants, which included the use of an absorbable plate (Synthes Inc, West Chester, PA, USA) in the first step and an ultrathick dermal allograft (Synthes Inc, West Chester, PA, USA) 3 years later in addition to a Goretex mesh [15]. In the context of cardiac comorbidities, the use of Goretex may be reasonable because repeated cardiac interventions will be required, allowing removal or replacement of the nonabsorbable material.…”
Section: Discussionmentioning
confidence: 98%
“…Multiple approaches to sternal cleft repair have been described, most of which used a single-stage technique, and some included the use of different types of mesh [13,14]. One recent case series reported staged sternal cleft closure in 2 infants, which included the use of an absorbable plate (Synthes Inc, West Chester, PA, USA) in the first step and an ultrathick dermal allograft (Synthes Inc, West Chester, PA, USA) 3 years later in addition to a Goretex mesh [15]. In the context of cardiac comorbidities, the use of Goretex may be reasonable because repeated cardiac interventions will be required, allowing removal or replacement of the nonabsorbable material.…”
Section: Discussionmentioning
confidence: 98%
“…In older patients, the chest cavity is stiff and difficult to repair. Sliding chondrotomy and clavicle dislocation are effective and beneficial in elderly patients with chest wall stiffness because they increase chest wall compliance [ 19 , 20 ]. Partial or complete thymectomy is also sometimes required to reduce the risk of mediastinal compression during closure.…”
Section: Discussionmentioning
confidence: 99%
“…Both patients tolerated the procedure well, with seroma formation during subsequent follow-ups. 14 We have used a similar approach after an intraoperative trial that showed difficulty in harvesting an autologous rib graft affecting chest wall stability as discussed with the interdisciplinary team. Dermal matrix graft of higher mechanical properties (SurgiMend, Integra LifeSciences Inc.) was then utilized as a means to stabilize the cleft margin in 1 of the patients.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 11 , 12 The use of different prosthetic as well as biologic mesh grafts was also utilized to aid in the closure of such defects with variable outcomes. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%